2018
DOI: 10.1086/698930
|View full text |Cite
|
Sign up to set email alerts
|

Policy-Development Monopolies: Adverse Consequences and Institutional Responses

Abstract: This online appendix contains all formal proofs, as well as analysis of an extension of a model with alternative assumptions about bargaining. We begin by establishing a general result on optimal policy development in our baseline model and our model of internal capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
2
25
0
1
Order By: Relevance
“…The incumbent can gain more from a somewhat misaligned agent willing to choose a stable policy than from a perfectly aligned agent who provides no insurance benefit. This result is in the spirit of Hirsch and Shotts (2018) who found that politicians want overseers with contrasting policy preferences to policy entrepreneurs. However, our model lets the politician pick the agent (i.e., policy entrepreneur) instead.…”
Section: Introductionmentioning
confidence: 77%
“…The incumbent can gain more from a somewhat misaligned agent willing to choose a stable policy than from a perfectly aligned agent who provides no insurance benefit. This result is in the spirit of Hirsch and Shotts (2018) who found that politicians want overseers with contrasting policy preferences to policy entrepreneurs. However, our model lets the politician pick the agent (i.e., policy entrepreneur) instead.…”
Section: Introductionmentioning
confidence: 77%
“…10. This is akin to models of policy making with valence (e.g., Hirsch and Shotts 2012;2015), which have been employed to study, for example, interbranch bargaining (Londregan 2000), legislative policy making (Hitt, Volden, and Wiseman 2017), lobbying and special interest politics (Hirsch and Shotts 2018;Hübert and Rezaee n.d.), and bureaucratic expertise (Ting 2011;Turner 2017;2019a).…”
Section: A Model Of Unilateral Action With Bureaucracymentioning
confidence: 99%
“…Moreover, while some rival policy priorities are relatively well aligned and coordinated, others are not, in which case contradictory policies and agendas may be pursued simultaneously, even across the same institution. Levels of policy development (Hirsch and Schotts, 2017), policy coordination and integration (Mickwitz et al, 2009;Turnpenny et al, 2008) and policy implementation (Hampton, 2018;Schofield, 2001) vary enormously within and across institutions.…”
Section: Non-energy Policy Processesmentioning
confidence: 99%